Phase-field modeling of fracture for quasi-brittle materials - Jacinto Ulloa; Patricio Rodríguez; Cristóbal Samaniego; Esteban Samaniego (Underground Space, 2019)
This paper addresses the modeling of fracture in quasi-brittle materials using a phase-field approach to the description of crack topology. Within the computational mechanics community, several studies have treated the issue of modeling fracture using phase fields. Most of these studies have used an approach that implies the lack of a damage threshold. We herein explore an alternative model that includes a damage threshold and study how it compares with the most popular approach. The formulation is systematically explained within a rigorous variational framework. Subsequently, we present the corresponding three-dimensional finite element discretization that leads to a straightforward numerical implementation. Benchmark simulations in two dimensions and three dimensions are then presented. The results show that while an elastic stage and a damage threshold are ensured by the present model, good agreement with the results reported in the literature can be obtained, where such features are generally absent. Keywords: Quasi-brittle materials, Fracture, Variational formulation, Phase fields, Gradient damage